Vibrational Dynamics of the Diterpene-Neoandrographolide. Issue 1 (2009) - Singh, P. K.; Hasan, Tanveer; Misra, Neeraj
Abstract : A complete normal coordinate analysis was performed for neoandrographolide in terms of the calculation by using Wilson's G-F matrix method and Urey Bradley force field. Andrographis paniculata has been reported for its potent hepatoprotective. Andrographis paniculata has been reported to have antisecretory (antidiarrhoeal), immunostimulant, antimalarial, antifilarial activity. It is also reported to have anticancer, anti HIV, anti-inflammatory, hypotensive action. In addition, it has found to be effective in myocardial infraction.